Patient safety culture: development and evaluation of an intervention to enhance nurses’ perception on handoffs and safety in katsina state public hospitals, north-western Nigeria - Kaware, Musa Sani (2024)
Patient safety entails preventing avoidable harm during healthcare delivery and has become a pressing concern in the healthcare sector due to growing awareness of potential risks and errors. In Nigeria, the burden of unsafe care carries profound consequences, including medical errors, infections, prolonged hospital stays, elevated healthcare costs, and reduced patient quality of life. This study determined the level of patient safety culture, identified factors linked to negative perceptions of this culture, developed and validated an educational intervention module, and evaluated its effectiveness among nurses in Katsina State Public Hospitals, North-West Nigeria. In Phase I, a cross-sectional study employing the Hospital Survey on Patient Safety Culture (HSOPSC) assessed patient safety culture among 430 nurses across 20 hospitals. Data analysis, performed using SPSS v.23, described the background and job-related characteristics of respondents and their perception of patient safety culture. Simple and multiple logistic regression analyses identified factors associated with negative perceptions. In Phase II, a Delphi technique validated the developed educational intervention module. In Phase III, a Quasi-Experimental design was employed to evaluate the intervention's effectiveness on nurses' perceptions of patient handoff and safety. Repeated-measures ANOVA was used to assess the intervention's impact, with a significance level set at α = 0.05. The study revealed that a majority of participants were female (59.8%), aged 30–39 years. Most had 1–5 years of hospital experience, with 46.4% working 40–59 hours per week. Nearly all (96.9%) had direct patient contact. The study identified four factors that were significantly associated with overall negative perceptions of patient safety culture. These include nurses who reported fewer events (five or less) in last 12 months with adjusted odds ratio of 2.66, (95% CI = 1.03–4.97), organizational learning and continuous improvement 2.39 (95% CI = 1.40–4.10), staffing 3.15 (95% CI = 1.34–7.17), and patient handoffs and transitions 1.48 (95% CI = 1.09–3.12). The educational module achieved good content validity. Repeated-measures ANOVA indicated significant mean differences across three assessment time points (pre-intervention, 3.05±0.32, post-intervention, 3.43±0.45, Follow-up, 3.34±0.40), with the educational intervention producing significant effects, F Stat 67.58, p<0.001. The post-hoc pairwise comparison, using the Bonferroni correction, revealed statistically significant mean differences in patient handoffs and safety perception scores across assessment time points. In conclusion, this study highlights the significance of addressing patient safety culture among nurses in Nigerian public hospitals. It identifies areas for improvement in patient safety culture and effectively develops, validates, and demonstrates the educational intervention module's ability to enhance patient handoff and safety perceptions among nurses. Thus, it should be integrated into nursing education and practice to enhance healthcare quality and reduce adverse events in Nigeria.